40Ar/39Ar dating of Quaternary volcanic rocks in Samoa. Issue 3 (3rd July 2022) - Gale, S. J.; Miggins, D. P.; Fepuleai, A.
ABSTRACT: Research on the Samoan volcanic lineament has focussed on shield volcanism and the volcanic origins of the island chain, and has largely ignored the middle and late Quaternary lavas that dominate the islands of Savai'i and Upolu. Yet these rocks may hold clues to the timing, origins and nature of rejuvenation volcanicity and to important questions of ocean island geochemistry and geodynamics. Upolu is particularly interesting for it possesses both shield-stage and rejuvenation-stage lavas. Although the chronology of shield volcanism is well-established, little is known of its history of rejuvenation volcanicity. The 40 Ar/ 39 Ar ages of 131.5 ± 7.3 ka (±2 s ) and 138.7 ± 2.7 ka (±2 s ) from the compound volcano of Mount Lanotō in southeast Upolu represent the first geochronometric determinations on the rejuvenation-stage lavas of the island. These cast doubt on the last glacial age assigned to the Mulifanua Volcanics formation and provide the first ages for the lavas erupted from the axial rift zone that dominates the island's geomorphology. These ages offer cautious endorsement of the proposition that rejuvenation-stage volcanicity was initiated on the westernmost of the Samoan islands and propagated east. Support for this belief comes from the systematic westward increase in the incidence of rejuvenation-stage lavas along the island chain.